Competitive Strategy In Increasing Company Profit (Study of delta nusantara Photo Copy Business in the Campus Environment of Kiai Haji Achmad Siddiq State Islamic University Jember) - Ahmad Hazin; Moch. Chotib; Misbahul Munir (Cita konsultindo, 2024)
The business world is increasingly urging entrepreneurs to be more professional and intelligent in understanding industrial and service market competition. In this case, the apostle of Allah has set an example of how to do business in accordance with the corridors of religion, saying honest, friendly, trustworthy and not reducing the dose to avoid problems arising from unfair competitive practices. Corporate strategy, especially competitive strategy is the right step that must be taken and realized by every company that wants to survive in the market. Therefore, the focus of this research is: 1. How is the competition strategy of Photo Copy delta archipelago in increasing company profits in the UIN Khas Jember Campus environment? 2. How are the supporting and inhibiting factors for entrepreneurs in increasing the profit of the company Photo Copy Delta archipelago in the UIN Khas Jember Campus environment ?. The research method used is descriptive qualitative research, which is research whose specifications explain in a systematic, structured, and clearly planned manner. Thus the strategy of competition between digital printing entrepreneurs, Delta archipelago has tips that are considered strategic. Namely through price competition, customer service, the threat of new competitors, product threats, bargaining power and rivalry between competitors. Furthermore, the supporting and inhibiting factors, which are carried out by Delta in this position, namely by analyzing strengths and weaknesses, as well as analyzing opportunities and threats that will occur.